GAME PANJOL BERBASIS ANDROID UNTUK MENINGKATKAN KARAKTER BERSAHABAT PADA SISWA SEKOLAH DASAR - Much Arsyad Fardani; Ika Ari Pratiwi; Zuhdan Kun Prasetyo; Samsuri Samsuri; Tutik Khotimah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study was to determine the increase in friendly character in elementary school students after learning to use the Panjol game.The research method used is the experimental research method. The type of experimental research used is the one group pretest-posttest design. The researcher gave a pretest before the treatment and gave a posttest after the treatment using the Panjol game. The treatment was given for three meetings in order to get the maximum result of increasing friendly character. The population in the study were students at SD 1 Muhammadiyah Kudus. Determination of the sample using purposive sampling technique with the criteria of grade IV students so that the sample in the study was 24 children in grade IV SD 1 Muhammadiyah. Data collection techniques in this study are observation, non-test, and interviews. The instruments used in this study were observation sheets and questionnaire sheets. The data obtained were then analyzed using the N-Gain test.The results showed an increase in the friendly character of children after treatment using the Panjol game. The increase in child-friendly character can be seen from the average pretest score of 39 and an increase in the average posttest score of 68. Meanwhile, the N-Gain value is 0.47 in the medium category.